Hate Speech on Social Media: An Exploration Problem, Consequences and Recommendation Solution - Indah, Tiara; Megantoro, Andrian Yohana; Putra, Romi Iriandi (Universitas Muhammadiyah Surakarta, 2023)
The purpose of this article is to explain some of the problems of hate speech carried out on social media; the author also tries to explain some recommendations that can potentially overcome hate speech carried out on social media. The data collection in this article was conducted through a literature study, and the result was that the current phenomenon is that social media users are more willing to express opinions or comment on other people who are not even known personally. The death of Sulli, a Korean idol, in October 2019 due to depression due to continuously receiving hate speech messages on her social media account became the most shocking case. In Indonesia, hate speech cases are dominated by defamation, harassment, slander, provocation, and threats against individuals and groups. There are at least four recommended solutions to this problem; the first is related to government regulations. Secondly, it is necessary to hold socialization, whether carried out by Digital Literacy activists, academics, or anyone who can influence the surrounding environment; socialization is not only carried out directly but is carried out on social media in the form of disseminating content. Third, the features of social media should be maximized because, currently, various types of social media have provided features to reduce negative comments, such as comment filters, spam reports, and several other features. And the last one is related to the ethics of interpersonal communication on social media.